This is how it always is [compact disc, unabridged] - Frankel, Laurie (Macmillan Audio, 2017)
When Rosie and Penn and their four boys welcome the newest member of their family, no one is surprised it's another baby boy. At least their large, loving, chaotic family knows what to expect. But Claude is not like his brothers. One day he puts on a dress and refuses to take it off. He wants to bring a purse to kindergarten. He wants hair long enough to sit on. When he grows up, Claude says, he wants to be a girl.